Catalytic covalent organic frameworks via pore surface engineering - Xu, Hong; Chen, Xiong; Gao, Jia; Lin, Jianbin; Addicoat, Matthew; Irle, Stephan; Jiang, Donglin (Chemical communications (Cambridge, England), 2014)
We report a synthetic strategy for construction of the first example of organocatalytic covalent organic frameworks via pore surface engineering. The COF catalyst combines a number of striking features, including enhanced activity, broad applicability, good recyclability, and high capability, to perform catalytic transformation under continuous flow conditions.